2023
DOI: 10.1186/s12888-023-05057-4
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of suicide resilience and meaning in life on the association between entrapment and suicidal ideation in Chinese patients with ovarian cancer: a cross-sectional study

Abstract: Background Numerous studies have confirmed that patients with ovarian cancer have a relatively high risk of suicidality. Early identification of psychological factors related to suicidal ideation in patients with ovarian cancer may provide effective information for suicide prevention strategies. This study aimed to investigate whether and how suicide resilience and meaning in life moderate the relationship between entrapment and suicidal ideation in patients with ovarian cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Studies have shown that resilience has a positive influence on social engagement in individuals with higher levels of hope (Çiçek, 2021;Yıldırım and Arslan, 2022). As advances in early diagnosis and treatment have led to increased survival rates for cancer patients compared to the past, resilience can positively affect survival outcomes (Zhang et al, 2023). In light of the widespread occurrence of breast cancer and the undeniable importance of resilience, the task of discerning the elements that shape resilience in women grappling with this condition takes on a paramount role.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that resilience has a positive influence on social engagement in individuals with higher levels of hope (Çiçek, 2021;Yıldırım and Arslan, 2022). As advances in early diagnosis and treatment have led to increased survival rates for cancer patients compared to the past, resilience can positively affect survival outcomes (Zhang et al, 2023). In light of the widespread occurrence of breast cancer and the undeniable importance of resilience, the task of discerning the elements that shape resilience in women grappling with this condition takes on a paramount role.…”
Section: Introductionmentioning
confidence: 99%